Are They Still Friends? Friendship Stability of Adolescents With Chronic Pain: 1-Year Follow-Up - Forgeron, Paula A.; Dick, Bruce D.; Chambers, Christine; Cohen, Janice; Lamontagne, Christine; Finley, Gordon Allen (Frontiers in Pain Research, 2022)
Most adolescents identify their best friend as their main source of social support. Adolescents with chronic pain (ACP) report the loss of friendships due to pain. Friendships protect against loneliness and depression, yet adolescents with pain experience increased levels of loneliness and depression compared to peers. This longitudinal study examines the friendship stability of dyads that included an adolescent with chronic pain compared to non-pain friendship dyads as well as the factors contributing to a friendship breakup. Eighty-three participants from 61 same-sex friendship dyads across 3 sites participated in a 1-year follow-up survey designed to capture friendship features, indices of social-emotional well-being, pain characteristics, and friendship stability. Chi-square, repeated measures ANOVA, and logistic regression were used to analyze the data. Dyads that included an ACP experienced higher rates of friendship breakup. The shorter length of friendship and having chronic pain predicted a friendship breakup at time 2. ACP continues to experience worse scores on indices of social-emotional well-being that are not predicted with a friendship breakup. Understanding what contributes to positive long-term friendships for those with pain may inform strategies to maintain and improve friendships for those with pain and who experience social challenges.